The clinical value of Vav3 in peripheral blood for predicting lymphatic metastasis of gastric cancer - Tan, B; Li, Y; Wang, C; Tan, M; Fan, L; Zhao, Q; Wang, D; Jia, N (British journal of biomedical science, 2017)
Overexpression of Vav3, a gene involved in signal transduction, promotes invasion and inhibits apoptosis in several cancers. The clinical value of the protein product of this gene, Vav3, in the peripheral blood of gastric cancer patients is unknown. We hypothesised increased serum Vav3 that related to tissue levels and lymph node metastases. In addition, we further explored its clinical value in respect of linked molecules Rac-1, MMP-7 and ICAM-1 Methods: 120 gastric cancer patients who had radical surgery were enrolled. Immunohistochemistry was used to determine the expressions of Vav3, Rac-1, MMP-7 and ICAM-1 in gastric cancer mucosa and normal mucosa. ELISA was used to detect these proteins in peripheral blood of gastric cancer patients and 100 age- and sex-matched healthy controls. Vav3, Rac-1 and MMP-7 (P < 0.001), but not ICAM-1 (P = 0.303) were more highly expressed by cancer tissues than normal gastric mucosa. Serum levels of all molecules were higher than those in healthy subjects (P < 0.001). Levels of Vav3, Rac-1 and MMP-7 decreased 2 weeks postoperatively (all P < 0.001) but there was no change in ICAM-1 (P = 0.192). Similarly, increased levels of Vav3, Rac-1 and MMP-7 were present in patients with lymphatic metastasis than those without (all P < 0.001) but there was no difference in ICAM-1 levels (P = 0.378). There were positive correlations between Vav3 with Rac-1 and MMP-7 in cancer tissues (P < 0.001), and also between Vav3 and Rac-1 in pre-surgery blood (P = 0.003). Vav3 in peripheral blood may serve as a biomarker for gastric cancer, and to predict the lymphatic metastasis in gastric cancer.